A new hermit crab species of the genus Catapagurus (Crustacea: Decapoda: Anomura: Paguridae) from the Ryukyu Islands, southern Japan - Komai, Tomoyuki; Osawa, Masayuki (Zootaxa, 2009)
A new species of the pagurid hermit crab genus Catapagurus A. Milne-Edwards, 1880, C. insolitus, is described and illustrated based on specimens from shallow waters in Okinawa Island, the Ryukyus. It belongs to an informal species group characterized by the possession of blade-shaped ambulatory dactyli, and is morphologically most similar to C. kosugei (Asakura, 2001). However, the new species is unique within the genus in having a multispinose antennal acicle, rarely seen in species of the family Paguridae.